Pedagogies of solidarity: service-learning model for social transformation. A view from the university - Pirela-Hernández, Ana (2023)
The accelerated changes currently experienced by societies in general have significantly affected the educational field, causing the expiration of conventional educational paradigms, conceiving the rethinking of their theoretical and practical nature as an imperative need in the educational system.  Therefore, and as an alternative to face these new learning needs, the objective of this research was to analyze the usefulness of solidarity pedagogies from the perspective of the university as a model of service learning for social transformation. In order to respond to the stated objective, a qualitative type of research was used, with descriptive scope and documentary type design, based on primary documentary sources, the technique of review and analysis of the information collected was used to support the theoretical bases of this research. Among the most important findings, it can be mentioned that those pedagogies that are applied from the principle of solidarity contribute to form people more committed to make significant contributions to the society in which they develop. Finally, it was concluded that solidarity pedagogies are innovative forms of learning oriented to the service of society, originated from the need to achieve an alternative that promotes social growth and development; they are models of intervention that not only promote social progress, but also improve the quality of education and the formation of values and principles in those involved.